Philosophy of Science, scientific realism and the survival of logical empiricism - Juan Vicente, (Analysis. Journal of Philosophical Research, 2019)
Book Review:Mauricio Suárez, Filosofía de la ciencia: historia y práctica. Madrid: Tecnos, 2019, 216 pp.